Proteinuria reduction by and safety of finerenone in Chinese patients with CKD without diabetes: a real-world retrospective study - Guangting Cong; Yue Qin; Xingzhi Wang; Manshu Sui (BMC Urology)
Abstract Background This retrospective study aimed to assess the effectiveness and safety of finerenone in patients with chronic kidney disease (CKD) without diabetes mellitus (DM), as evidence from both clinical trials and real-world data remains limited. Methods Patients with CKD and without DM were enrolled in this study from December 2022 to August 2023. In addition to standard CKD treatment, patients received finerenone. Twenty-four-hour urinary protein (UTP) levels, estimated glomerular filtration rate (eGFR), and serum potassium (sK⁺) levels were measured on a monthly basis for 5 months from the time of enrolment. Results A total of 43 patients were enrolled, with a baseline 24-h UTP of 5.58 ± 7.67 g. The mean age of the patients was 50.98 ± 13.00 years, and 30 individuals (69.8%) were male. Membranous nephropathy was diagnosed in 20 patients (46.5%). During follow-up, the 24-h UTP levels significantly decreased, with a median reduction of 2.46 g (IQR: 0.2015–2.609; P < 0.01) and a percentage change of 60.86% (IQR: 35.625–87.062%) being observed. No significant changes were observed in the eGFR (P = 0.713) or sK⁺ levels (P = 0.400), which remained within a range of 3.5–5.5 mmol/L. No rehospitalizations due to hyperkalaemia occurred. Conclusion Finerenone treatment significantly reduced proteinuria over the follow-up period, with minimal effects on potassium and the eGFR being observed, thereby supporting its safety and efficacy in the treatment of CKD patients without DM.